IMPLEMENTASI TRANSPARANSI PENGELOLAAN KEUANGAN DAERAH DI KABUPATEN PONTIANAK - Rahmat E. 21109003, Agus (FISIP Universitas Tanjungpura, 2014)
The purpose of this study is to explain the financial management and accountability of financial performance and the factors that influence its implementation in Pontianak regency. The results of this study are: first, the policy implementation of financial management and accountability does not undergo significant obstacles. But in the case of budget execution principals of transparency, accountability and efficient is not optimal. Second: factors that affect the implementation of the budget is the principle of communication, there is no command to remove more detail, the factors that are less resource facility of computer software applications, and lengthy bureaucratic structure factors cause the disbursement of funds in addition to the current lack of Trustees less objektiv and independent in their assessments. Keywords : Implementation, Local Finance.